How can we relieve gastrointestinal symptoms in people with cystic fibrosis? An international qualitative survey. Issue 1 (7th September 2020) - Smith, Sherie; Rowbotham, Nicola; Davies, Gwyneth; Gathercole, Katie; Collins, Sarah J; Elliott, Zoe; Herbert, Sophie; Allen, Lorna; Ng, Christabella; Smyth, Alan
Abstract : Introduction: Relieving gastrointestinal (GI) symptoms was identified as a 'top ten' priority by our James Lind Alliance Priority Setting Partnership in cystic fibrosis (CF). We conducted an online survey to find out more about the effect of GI symptoms in CF. Methods: We co-produced an online survey distributed to the CF community via web-based platforms. The survey consisted of open and closed questions designed to help us learn more about the effects of GI symptoms for people with CF (pwCF). We analysed the data using descriptive statistics and thematic analysis. We promoted the survey via social media and web-based platforms which allowed respondents from any country to take part. Our participants came from the CF community, including: adults and children with CF, parents and close family of pwCF and healthcare professionals (HCPs) working with pwCF. Results: There were 276 respondents: 90 (33%) pwCF, 79 (29%) family, 107 (39%) HCPs. The most commonly reported symptoms by lay respondents were stomach cramps/pain, bloating and a 'combination of symptoms'. The top three symptoms that HCPs said were reported to them were reduced appetite, bloating and constipation. Almost all (94% (85/90)) HCPs thought medications helped to relieve GI symptoms but only 58% (82/141) of lay respondents agreed. Conclusions: Our survey has shown that GI symptoms among our participants are prevalent and intrude on daily lives of pwCF. There is a need for well-designed clinical studies to provide better evidence for management of GI symptoms and complications.